2011
DOI: 10.1097/pai.0b013e318214e523
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Sealing and Cooling as Methods to Preserve Surgical Specimens

Abstract: Recently, vacuum-based preservation of surgical specimens has been proposed as a safe alternative to formalin fixation at the surgical theater. The method seems feasible from a practical point of view, but no systematic study has examined the effect of vacuum sealing alone with respect to tissue preservation. In this study, we therefore subjected tissue samples from 5 different organs to treatments with and without vacuum sealing and cooling at 4°C to study the effect of vacuum sealing of surgical specimens wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…From our experience on nucleic acid preservation [7], [9] it seems that it is the prompt cooling that principally influences preservation. This has also been confirmed by independent observations [27] that show that storage at 4°C preserved tissues to a higher degree than storage at room temperature, independently of whether the tissue was subjected to vacuum sealing or not. With this study we prove that VPAC maintains cell viability even after 70 hours, however, as expected, for longer VPAC times, the percentage of cell death increased.…”
Section: Discussionsupporting
confidence: 70%
“…From our experience on nucleic acid preservation [7], [9] it seems that it is the prompt cooling that principally influences preservation. This has also been confirmed by independent observations [27] that show that storage at 4°C preserved tissues to a higher degree than storage at room temperature, independently of whether the tissue was subjected to vacuum sealing or not. With this study we prove that VPAC maintains cell viability even after 70 hours, however, as expected, for longer VPAC times, the percentage of cell death increased.…”
Section: Discussionsupporting
confidence: 70%
“…More extensive exposure of tissues to air, which occurs during conventional autopsies, could also have a negative influence on tissue quality. It is known that vacuum sealing of tissue specimens has a beneficial effect on RNA preservation [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Each step in this process is critical: this shed light on the role that is played by an organized team and a correct triage evaluation of the sample in the Pathology Room. The VPAC system, already proven to preserve specimens integrity, was adopted as gold standard procedure in order to obtain viable tissues [ 6 8 ]. However, while in breast cancer tissues RNA, DNA and proteins may be optimally preserved for >24h [ 7 , 13 ], we here showed that lung tissues are much more sensible to this time.…”
Section: Discussionmentioning
confidence: 99%
“…The specimens were preserved and transferred to the pathology lab using the vacuum packing and cooling (VPAC) procedure [ 6 , 7 ]. Briefly, in the OR, explanted surgical specimens were immediately placed into beta-ray sterilized plastic bags and vacuum-sealed using the TissueSAFE machine (Mod.…”
Section: Methodsmentioning
confidence: 99%